2009
DOI: 10.1200/jco.2008.17.8251
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Epidermal Growth Factor Receptor Antisense DNA Therapy in Head and Neck Cancer: First Human Application and Potential Antitumor Mechanisms

Abstract: A B S T R A C T PurposeSquamous cell carcinoma of the head and neck (SCCHN) is characterized by upregulation of the epidermal growth factor receptor (EGFR). We developed a novel strategy to target EGFR by using a therapeutic gene that consisted of an EGFR antisense (AS) gene sequence under U6 promoter control. A phase I clinical trial was conducted to evaluate the safety and biologic effects of EGFR AS. Patients and MethodsPatients with advanced SCCHN who were refractory to standard therapies and who had at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 29 publications
2
51
0
1
Order By: Relevance
“…In a cohort of twenty patients, no grade 3 or 4 toxicities were reported. In addition, median survival was 5.4 months [85]. The disease-control group, as defined by complete remission, partial remission, or stable disease, demonstrated a median survival of 7.9 months as compared to 3.4 months for the partial disease group [85].…”
Section: Antisense Oligonucleotides and Sirnamentioning
confidence: 99%
“…In a cohort of twenty patients, no grade 3 or 4 toxicities were reported. In addition, median survival was 5.4 months [85]. The disease-control group, as defined by complete remission, partial remission, or stable disease, demonstrated a median survival of 7.9 months as compared to 3.4 months for the partial disease group [85].…”
Section: Antisense Oligonucleotides and Sirnamentioning
confidence: 99%
“…Plasmid DNA encoding an EGFR antisense fragment was injected intratumorally into HNSCC xenografts, resulting in antitumor effects (He et al, 1998). On the basis of these studies a dose escalation phase I clinical trial was carried out with intratumoral administration of the EGFR antisense plasmid DNA (Lai et al, 2009). No dose-limiting toxicity was observed at any of the doses.…”
Section: Gene Excision Therapymentioning
confidence: 99%
“…Results from a phase I trial using local delivery of a plasmid encoding antisense RNA against the EGFR to treat HNSCC have been published recently (Lai et al, 2009). Although these findings need to be borne out in larger trials, they showed a 30% response rate (versus 10-15% response to other anti-EGFR therapies).…”
Section: Prodrug Sensitizationmentioning
confidence: 94%